Terminator field‐aligned currents: A new finding from the Ionospheric Dynamics and Electrodynamics Data Assimilation Model. Issue 6 (3rd June 2014) - Zhu, L.; Schunk, R. W.; Eccles, V.; Scherliess, L.; Sojka, J. J.; Gardner, L.
Abstract: A new field‐aligned current system in the high‐latitude ionosphere has been discovered. The finding was based on the reconstructions from the Ionospheric Dynamics and Electrodynamics Data Assimilation Model with the ingestion of ground‐based magnetometer measurements. The new current system develops and evolves along the ionospheric terminator, and it is thus termed as the terminator field‐aligned currents. This is the first field‐aligned current system in the high‐latitude ionosphere that is not directly driven by the magnetospheric dynamics and has an ionospheric origin. The study of it will help us to explore the active role of the ionosphere in the magnetosphere‐ionosphere coupling and improve the physical understanding of the electrodynamics and plasma dynamics of many small‐scale structures in the polar ionosphere. Key Points: It is the first time that the terminator current system is discovered The finding is based on the reconstructions from a data assimilation model The first ionosphere‐originated field‐aligned current in the polar ionosphere